1998
DOI: 10.2138/am-1998-11-1242
|View full text |Cite
|
Sign up to set email alerts
|

Novel nano-organisms from Australian sandstones

Abstract: We report the detection of living colonies of nano-organisms (nanobes) on Triassic and Jurassic sandstones and other substrates. Nanobes have cellular structures that are strikingly similar in morphology to Actinomycetes and fungi (spores, filaments, and fruiting bodies) with the exception that they are up to 10 times smaller in diameter (20 nm to 1.0 m). Nanobes are noncrystalline structures that are composed of C, O, and N. Ultra thin sections of nanobes show the existence of an outer layer or membrane that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…Similar structures described as ''nannobacteria'' were also reported to abound in calcium carbonate (15) and sulfides sediments (16) where they were seen as overlooked factors affecting geochemical cycles. Other authors reported the presence of so-called ''nanobes,'' a purported form of nanoscopic actinomycete-like microorganisms, which supposedly grow on Triassic and Jurassic sandstones (17). Similar nanoparticles and polycyclic aromatic hydrocarbons were also detected in meteorite fragments from Mars, leading to the hypothesis that these structures represent fossilized bacteria (18).…”
mentioning
confidence: 97%
“…Similar structures described as ''nannobacteria'' were also reported to abound in calcium carbonate (15) and sulfides sediments (16) where they were seen as overlooked factors affecting geochemical cycles. Other authors reported the presence of so-called ''nanobes,'' a purported form of nanoscopic actinomycete-like microorganisms, which supposedly grow on Triassic and Jurassic sandstones (17). Similar nanoparticles and polycyclic aromatic hydrocarbons were also detected in meteorite fragments from Mars, leading to the hypothesis that these structures represent fossilized bacteria (18).…”
mentioning
confidence: 97%
“…More recently, novel nano-organisms (nanobes) have been described growing on Triassic and Jurassic sandstones collected from petroleum exploration boreholes off the Western Australian coast (Uwins et al, 1998). These cells (20-150 nm in diameter) provide further evidence in strong support of nano-scopic life.…”
Section: Biodiversity Of New South Wales Subterranean Faunamentioning
confidence: 99%
“…Over the following years, various publications proposed the existence of 'nannobacteria' (or nanobes) in terrestrial samples 2 , sometimes with implied medical 3 and environmental 2 significance. However, a lack of solid biological evidence for the existence of cells considered to be too small to accommodate sufficient genomic DNA, RNA, proteins and solvent for life consigned nanobacteria to the scientific fringe ('the cold fusion of microbiology' 4 ).…”
mentioning
confidence: 99%